1996
DOI: 10.1177/030006059602400601
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Insulin, Glucose and Serum Uric Acid and Their Contribution to the Progression of Renal Damage in Patients with Primary Glomerulonephritis

Abstract: It is known that some metabolic disturbances may modify the progression of renal disease including primary glomerulonephritis, but the role of purines in this process is still unknown. To investigate this, 13 untreated patients with primary glomerulonephritis were followed up for a mean of 17.6 months to analyze the changes in proteinuria and glomerular filtration rate. On entering the study, each patient was given an oral glucose tolerance test and an oral fructose load test. The areas under the glucose (PGA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…6) and in multiple regression analysis (table 2). Manitius et al [13]suggest that purine metabolism may modulate the progression of renal disease in proteinuric patients.…”
Section: Discussionmentioning
confidence: 99%
“…6) and in multiple regression analysis (table 2). Manitius et al [13]suggest that purine metabolism may modulate the progression of renal disease in proteinuric patients.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies it was shown that hyperuricemia-induced tubulointerstitial damage is strongly associated with hypertension and salt sensitivity [4, 5]. Our previous study [6] showed that uric acid may be involved in the progression of renal disease in proteinuric patients. Because intrarenal vessel dysfunction plays crucial role in the damage to the interstitium, it seems reasonable to evaluate the association between uric acid and renal vessel function in patients with IgA nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Blood was collected at 0, 30, 60 and 120 min for uric acid determination. Plasma uric acid area Studies were carried out in 25 untreated pateints with mild primary (essential) hypertension according to the WHO classifica-(PUAA) under the curve was calculated according to a previously used method [17]. tion.…”
Section: Methodsmentioning
confidence: 99%